LAS CINEMATOGRAFÍAS MINORITARIAS Y MINORIZADAS EN LA POLÍTICA CULTURAL DE LA UNIÓN EUROPEA: LA ALTERNATIVA DANESA - Dra. Antía Mª LÓPEZ GÓMEZ ,Dr. Enrique CASTELLÓ MAYO,Mgt. Inés ARIAS IGLESIAS (Fonseca, Journal of Communication, 2023)
The purpose of this document is to analyze the European Union's approach to its cultural development model during the last decade and towards the future. Based on the analysis of mass cultural models, which dominate the post-modern democracies, we suggest that the dissident forms of culture (minorities or minoritised), precisely for their refractory condition towards the cultural standardized model and generated by the current political and economic logic, constitute a guarantee for the possibility, after modernity, of a different European culture.